2021
DOI: 10.1002/lpor.202100057
|View full text |Cite
|
Sign up to set email alerts
|

High Speed Evanescent Quantum‐Dot Lasers on Si

Abstract: Significant improvements in III–V/Si epitaxy have pushed quantum dots (QDs) to the forefront of Si photonics. For efficient, scalable, and multifunctional integrated systems to be developed, a commercially viable solution must be found to allow efficient coupling of the QD laser output to Si waveguides. In this work, the design, fabrication, and characterization of such a platform are detailed. Record‐setting evanescent QD distributed feedback lasers on Si with a 3 dB modulation bandwidth of 13 GHz, a threshol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 50 publications
(49 reference statements)
0
49
0
Order By: Relevance
“…Besides intensively studied broad area lasers, narrow ridge lasers that guarantee fundamental transverse electronic mode lasing are now garnering more attention [82][83][84]. Reducing the ridge width down to a few microns, a lower threshold current and better heat dissipation are also expected due to the reduced injection area and efficient current confinement.…”
Section: Fp Lasermentioning
confidence: 99%
“…Besides intensively studied broad area lasers, narrow ridge lasers that guarantee fundamental transverse electronic mode lasing are now garnering more attention [82][83][84]. Reducing the ridge width down to a few microns, a lower threshold current and better heat dissipation are also expected due to the reduced injection area and efficient current confinement.…”
Section: Fp Lasermentioning
confidence: 99%
“…The same authors demonstrated a transfer rate of 25 Gb/s using eight-layer high-density QD lasers. These superior characteristics indicate that QD lasers are promising as future light sources in low-cost and low-power-consumption applications [ 152 , 153 ]. Moreover, improving the modal gain of QD lasers is of great significance for achieving a higher speed.…”
Section: Physics and Device Properties Of Qdsmentioning
confidence: 99%
“…(b) Cross-sectional FIB-SEM image at the hybrid session for a heterogeneous integrated QD DFB laser. Reprinted with permission from ref . Copyright 2021 Wiley VCH.…”
Section: Fundamental Advantages Of the Qd Active Regionmentioning
confidence: 99%
“…By engineering the Si grating designs, rapidly increasing performance is shown in heterogeneously integrated QD DFB lasers: a side-mode-suppression ratio (SMSR) of 40 dB is achieved based on second order surface gratings, 55 a SMSR of 61 dB and a Lorentzian line width of 211 kHz is achieved based on a shallow etched firstorder grating, 56 a SMSR of 60 dB and a Lorentzian line width of 26 kHz is achieved based on first-order side-hole gratings. 49 The Lorentzian line width of tens of kHz is low compared to the typical solitary QW laser line width of several megahertz, attributed to the much lower α H of QDs. In addition, this value also significantly outperforms QD DFB lasers without a Si waveguide, that is, 480 kHz in ref 57 Similarly, the combinations of different Si external cavity designs and the QD active region prove to be effective ways to simultaneously provides the tuning mechanism of the laser as well as the line width reduction.…”
mentioning
confidence: 94%